Biology, Spatial Distribution and Range Expansion of Acraea terpsicore (Linnaeus, 1758) (Nymphalidae: Heliconiinae) in Borneo - Sabina, Noor (Universiti Malaysia Sarawak(UNIMAS), 2018)
The Tawny Coster, Acraea terpsicore (Linnaeus, 1758) is one of the prominent species from the tribe Acraeini, which is widely distributed throughout the Indian and Sri Lankan region. In the past three decades, its distribution range has expanded southwards through Southeast Asia and Australia. This non-indigenous Nymphalid butterfly was first detected in 2013 in Sarawak, on the Borneo Island. This study aimed to the findings of biological and ecological aspects of A. terpsicore in support of its current establishment in Borneo. A comparative biology relative to habitat types, phenotype and gender was conducted on the populations of A. terpsicore in Sarawak. This study reveals that the biology of A. terpsicore is similar to those reported from other regions of its novel range (Southeast Asian and Australian). Biological control and pest management strategies are better performed if precise information about interactions of an invasive species in a newly invaded environment are available in real time. This non-indigenous species was found to feed voraciously on Passiflora foetida in Sarawak. The host plant association and feeding preference studies showed that this species prefers to feed on its primary host plant from the family Passifloraceae and currently, it is unlikely to pose as a pest of economic importance. Species Distribution Modeling (SDMs) forecasting the current and future climatically habitable range of A. terpsicore showed promising future range of this species, which is likely to expand further southwards to Sulawesi Island, the Philippines and northwards to Taiwan. The genetic variance of A. terpsicore among the population of Borneo and adjacent areas was executed at the level of partial mitochondrial genome (COI). Pairwise genetic distance and phylogenetic analysis among the populations of A. terpsicore showed no genetic variance. This is due to the species may be too recent and young with higher gene flow among the population and is still in the establishment phase of invasion. A. terpsicore should be closely monitored in the future as this species is still in the initial phase of invasiveness and can be a threat at any point in future for becoming a pest of economic importance.